2021
DOI: 10.1371/journal.pone.0251698
|View full text |Cite
|
Sign up to set email alerts
|

Religious affiliation and suicidality among college students in China: A cross-sectional study across six provinces

Abstract: Background Several past studies indicated that religious beliefs, orientation, and practice are protective of suicide. Findings from recent studies in China suggest that religiosity may contribute to increased suicidality. However, few studies have examined the associations between religious affiliation across different faiths and suicidality in China. Objective The current study examines the association between religious affiliation and suicidality among college students in six provinces in China. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Nevertheless, some nations have lower suicide rates, not necessarily because of poor reporting and recording of the cause of death. Lester (8) reviewed research on suicide in Muslim countries and found that the suicide rate was consistently low in countries where Islam was the predominant religion, and the protectiveness of Islam against suicide has been confirmed by other scholars (9)(10)(11)(12). Therefore, the effect of poor reporting and recording of the cause of death, and the higher odds of undetermined, accidental, and other violent mortality rates as possible sources of underreported suicides, may be factors influencing the lower suicide rates reported in Muslim countries (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some nations have lower suicide rates, not necessarily because of poor reporting and recording of the cause of death. Lester (8) reviewed research on suicide in Muslim countries and found that the suicide rate was consistently low in countries where Islam was the predominant religion, and the protectiveness of Islam against suicide has been confirmed by other scholars (9)(10)(11)(12). Therefore, the effect of poor reporting and recording of the cause of death, and the higher odds of undetermined, accidental, and other violent mortality rates as possible sources of underreported suicides, may be factors influencing the lower suicide rates reported in Muslim countries (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Malaysia had the highest average SR ratio:1.7 compared to the other nine majority Muslim countries (average rate ratio range of 0.4-1.0) [12]. In other age groups, Muslims reported decreased suicidality (B = -0.034, p = 0.031) compared to Christianity and Buddhism among university students in China [26]. Some studies show disparities and differences in SR across ethnicity in the United Kingdom [27], in the United States [28], and in Singapore [17], and the relationship has been consistent and explored in other countries [29].…”
Section: Discussionmentioning
confidence: 91%
“…Similar results were observed among medical students, in which spirituality was also associated with a lower risk for suicidal ideation (Wachholtz & Rogoff, 2013). This seems to be explained by the fact that spiritual well-being promotes positive feelings like happiness, existence, and optimism and acts protecting against the negative feelings of loneliness and social isolation (Lew et al, 2021).…”
Section: Discussionmentioning
confidence: 99%